The Influence of Perceived Ease of Use and Perceived Usefulness on E-Wallet Continuance Intention : Intervening Role of Customer Satisfaction - Olivia, Michelle; Marchyta, Nony Kezia (Institute of Research and Community Outreach - Petra Christian University, 2022)
The developments of information technology and the advent of new normal in Indonesia had transformed how transaction was conducted, increasing the importance of e-wallet. This study aimed to analyze the effect of perceived ease of use, perceived usefulness, and customer satisfaction on e-wallet continuance intention. This study focused on customers of e-wallets in Indonesia. This research was quantitative research with data collection used the purposive sampling technique. This sampling was conducted by distributing questionnaires to 97 e-wallet customers in Indonesia, with eight questionnaires being rejected due to unmet criteria. Partial Least Square Path Modeling (PLSPM) was used to test the hypotheses. The study found that perceived ease of use had a direct positive influence on continuance intention as well as an indirect positive influence on it through customer satisfaction as an intervening variable, perceived enjoyment did not directly influence continuance intention but had indirect positive influence on it through customer satisfaction as an intervening variable, and customer satisfaction positively influenced continuance intention